Efeitos da terapia led de baixa potência em ratas ovariectomizadas com trauma tendíneo: aspectos inflamatórios - Silva, Carla Helrigle (2013)
The aim of this experimental study was to investigate the effects of LED phototherapy on the inflammation process in the calcaneal tendon of ovariectomized rats (OVX) through the involvement of inflammatory mediators IL-6, IL-10 and TNF-α. Thirty-five female Wistar rats were divided into 4 groups: 3 ovariectomized groups, untreated (NTTA); treated (TTA) and control subdivided into experimental periods of 3 , 7 and 14 days, totaling 30 rats and one group (n = 5) not ovariectomized (not OVX). Tendinitis was induced by trauma using a 208g mass placed at 20 cm from the right tendon of each animal with energy of 0.70 J. The animals were treated 12 hours after tendonitis with LED therapy ( 945nm , power 32mW, energy of 3.84 J, power density of 0.06 W / cm ², energy density of 7.68 J / cm ², beam output area of 0.5 cm ² and time of 120 s) and every 48 hours at 3, 7 and 14 days. Then, euthanasia was performed in a CO2 chamber 24h after the last treatment. The tendons were dissected and stored in liquid nitrogen at -196ºC, thawed only at the time of immunoenzymatic test (ELISA). After analysis of results, groups treated with LED showed decrease in the number of pro-inflammatory cells, IL- 6 and TNF- α (p < 0.05) and increased number of anti-inflammatory IL -10 ( p <0.05) even when compared to the not OVX group (p < 0.05). It was concluded that low-intensity LED in the studied parameters has repairing effect on the tendinopathy process (tendonitis) caused by trauma in female rats (OVX).